Reflections on Leadership and Ethics in Complex Times. - Fairhurst, Gail T. (Atlantic Journal of Communication)
How do leaders make and justify decisions during exceedingly complex times? This question is examined through a focus on the roadblocks that leaders themselves throw in the way of their effectiveness; an ethical orientation that seems increasingly lacking; and the growing need for collaboration, clumsy solutions, and organizations dedicated to civil discourse.